The Role of Families and Nursing Homes in Improving the Quality of Life of The Elderly in Tanjungpinang City - Emmy Solina; Darsono Wisadirana; Wawan Edi Kuswandoro; Anif Fatma Chawa; Casiavera (International Journal of Educational Research Excellence (IJERE), 2024)
This research discusses the role of families and nursing homes in improving the quality of life of the elderly. Social problems facing the elderly include the ability of families and nursing homes to meet their needs. The elderly are part of the demographic bonus challenge and need support for physical, economic, psychological and social well-being. Shifts in family functions have led to an increase in the number of elderly people in nursing homes. The International Convention on the Elderly emphasizes the importance of access to basic needs and employment opportunities, but Indonesia has not ratified this convention, even though there are local policies that recognize the elderly as a vulnerable group that must be empowered. This research uses a constructivist paradigm and qualitative methods with in-depth interviews and participant observation to collect data. The results show that the pattern of caring for elderly people in families and nursing homes is different, with nursing homes often being a place for elderly people who have been neglected by their families. Families have an important role in caring for and supporting elderly people, which can significantly influence their quality of life. Nursing homes also play a role in providing care and support, but face challenges such as limited resources and social stigma. This research highlights the importance of a holistic approach in elderly care, both in the context of families and nursing home institutions. Well-functioning families and well-managed nursing homes can improve the quality of life of seniors, by taking into account their physical, emotional, social, and spiritual needs.